Do CEO Succession and Succession Planning Affect Stakeholders' Perceptions of Financial Reporting Risk? Evidence from Audit Fees - Bills, Kenneth L.; Lisic, Ling Lei; Seidel, Timothy A. (The Accounting Review, 2017)
ABSTRACT In this paper, we examine how CEO succession and succession planning affect perceptions of financial reporting risk among stakeholders who are responsible for and oversee firms' financial reporting (e.g., auditors, management, and audit committees). Management succession introduces uncertainty about firms' future operations, financial policies, and potential motivation for earnings management, which we predict elevates the perceived risk of financial reporting improprieties. Consistent with this prediction, we find that audit fees are higher for firms with new CEOs. Importantly, however, we note that careful CEO succession planning (i.e., promoting an “heir apparent”) attenuates perceptions of higher risk, as evidenced by a lack of an audit pricing adjustment. These results are robust to several alternative specifications and analyses designed to mitigate the concern that the association between audit fees and CEO succession and succession planning is driven by factors leading to the CEO change. We also show that audit fee increases dissipate over time as the new, non-heir CEO stays longer at the firm, reinforcing the inference that audit fees increase in response to the uncertainty surrounding a new CEO. Additionally, we do not find evidence of a deterioration in audit quality with new CEOs, independent of the succession plan. JEL Classifications: G30; M12; M41; M42.